Análisis de la sistematización del control de inventario en la jefatura de bodega del Gobierno Autónomo Descentralizado del Cantón Alfredo Baquerizo Moreno (Jujan) correspondiente al período 2019 - 2020 - Zamora Rodriguez, Julissa Maria (2020)
This case study was supported by research for the analysis of the inventory control systematization in the warehouse manager, for this reason the Laws, Codes, Regulations, and Standards in force which intervene in Inventory Control were reviewed, among the that the General Comptroller of the State, General Manual of Administration and Control of the Public Sector is evidenced, in addition, a discussion was held with the officials where it is analyzed that in the Autonomous Decentralized Municipal Government canton Alfredo Baquerizo Moreno Jujan there is disorganization in the inventories at the change of administration which induces a shortage of historical information in the entity's inventory of assets, which are disclosed as machinery, computer assets, office furniture, all being for the use of the institution, in the change of residence of the entity was verified the state of the same, discovering deficiencies and destruction of the goods, in addition systematization with the new assets in the inventory that were acquired by the entity, enter and exit by the weighted average method, the negative situation suffered by the warehouse manager is disclosed. The methodology used for the case study is descriptive and exploratory, because it allows observing various findings incurred during the process. The research techniques used were the interview and direct observation, which allowed the creation of the necessary data to make known that you need internal control, for the preparation of the general inventory.